2020
DOI: 10.1108/tqm-04-2019-0120
|View full text |Cite
|
Sign up to set email alerts
|

The Six Sigma framework improves the awareness and management of supply-chain risk

Abstract: PurposeModern supply chains are at risk as a result of increasing disturbance. The use of Lean and Six Sigma’'s values, methods and tools can be one option to analyze, prevent and mitigate risks. The purpose of this study is to investigate whether a combined Lean Six Sigma philosophy can support the awareness and management of supply-chain risk.Design/methodology/approachThe methodology followed in the study is based on a literature review and multiple case study, performed by means of qualitative methods of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Efficient process management and practicing operational excellence improves the reliability and capacity of processes (Bal et al , 2017; Beck et al , 2016). Developing LSS implementation routines, incorporating systematic problem solving, exploring novel solutions to continuously improve existing processes and innovating processes (via new technologies) results in reliable and resilient health care processes (Andersson and Pardillo-Baez, 2020; Hoerl and Gardner, 2010). LSS improves organizational resilience through the creation of efficient, reliable and resilient processes and continuous learning and improvement (Andersson and Pardillo-Baez, 2020; Pal et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Efficient process management and practicing operational excellence improves the reliability and capacity of processes (Bal et al , 2017; Beck et al , 2016). Developing LSS implementation routines, incorporating systematic problem solving, exploring novel solutions to continuously improve existing processes and innovating processes (via new technologies) results in reliable and resilient health care processes (Andersson and Pardillo-Baez, 2020; Hoerl and Gardner, 2010). LSS improves organizational resilience through the creation of efficient, reliable and resilient processes and continuous learning and improvement (Andersson and Pardillo-Baez, 2020; Pal et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…A primary goal of LSS is to identify and reduce process variation, and reduce risk through systematic process monitoring and control to reduce instability, uncertainty and lack of reliability that comes from excessive process variation. Organizations that adopt Six Sigma focus on developing personnel with improved risk management awareness, with a goal of risk reduction to an organization’s operations (Andersson and Pardillo-Baez, 2020). In turn, organizations often deploy LSS through their respective supply chains, resulting in improved risk reduction among those supplier’s risk reduction and improved supplier and customer collaboration in the supply chain (Andersson and Pardillo-Baez, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As indicated by Andersson and Pardillo-Baez (2020), LSS could provide benefits for risk mitigation, surveillance and risk prevention solutions. This research revealed the need to consider the prolonged external disruptions in the resource supply and demand such as what happened during the Covid-19 period as part of LSS-based risk management.…”
Section: Ijlss 124mentioning
confidence: 99%